Opportunities for adapting data write latency in geo-distributed replicas of multicloud systems - Kozina, Olha; Machado, José; Volk, Maksym; Heiko, Hennadii; Panchenko, Volodymyr; Kozin, Mykyta; Ivanova, Maryna (MDPI, 2025)
This paper proposes an AI-based approach to adapting the data write latency in multicloud systems (MCSs) that supports data consistency across geo-distributed replicas of cloud service providers (CSPs). The proposed approach allows for dynamically forming adaptation scenarios based on the proposed model of multi-criteria optimization of data write latency. The generated adaptation scenarios are aimed at maintaining the required data write latency under changes in the intensity of the incoming request flow and network transmission time between replicas in CSPs. To generate adaptation scenarios, the features of the algorithmic Latord method of data consistency, are used. To determine the threshold values and predict the external parameters affecting the data write latency, we propose using learning AI models. An artificial neural network is used to form rules for changing the parameters of the Latord method when the external operating conditions of MCSs change. The features of the Latord method that influence data write latency are demonstrated by the results of simulation experiments on three MCSs with different configurations. To confirm the effectiveness of the developed approach, an adaptation scenario was considered that allows reducing the data write latency by 13% when changing the standard deviation of network transmission time between DCs of MCS.
Keywords: multicloud systems; data writing latency; optimization; data consistency method